Embedded Systems Specification and Design Languages Selected Contributions from FDL'07 - Villar, Eugenio (Lecture Notes in Electrical Engineering, 2008)
FDL is the most important European and, probably, worldwide forum to present research results, to exchange experiences, and to learn about new trends in the application of specification and design languages and the associated design and modeling methods and tools for complex, heterogeneous HW/SW embedded systems. FDL'07 was the tenth of a series of successful events held all around Europe. FDL'07 was held in Barcelona, the capital city of Catalonia, Spain. The high number of submissions to the conference this year allowed the Program Committee to prepare a high quality conference program. Embedded Systems Specification and Design Languages includes a selection of the most relevant contributions based on the review made by the program committee members and the quality of the contents of the presentation at the conference. In many cases, the authors have improved the original content with additional technical information. The papers cover the most important aspects in system modeling and specification, an essential area in Embedded Systems design. The objective of Embedded Systems Specification and Design Languages is to serve as a reference text for researchers and designers interested in the extension and improvement of the application of design and verification languages in the area of Embedded Systems.